Roles of Noncoding RNAs in Regulation of Mitochondrial Electron Transport Chain and Oxidative Phosphorylation - Kobayashi, Ami; Takeiwa, Toshihiko; Ikeda, Kazuhiro; Inoue, Satoshi (International journal of molecular sciences, 2023)
The mitochondrial electron transport chain (ETC) plays an essential role in energy production by inducing oxidative phosphorylation (OXPHOS) to drive numerous biochemical processes in eukaryotic cells. Disorders of ETC and OXPHOS systems are associated with mitochondria- and metabolism-related diseases, including cancers; thus, a comprehensive understanding of the regulatory mechanisms of ETC and OXPHOS systems is required. Recent studies have indicated that noncoding RNAs (ncRNAs) play key roles in mitochondrial functions; in particular, some ncRNAs have been shown to modulate ETC and OXPHOS systems. In this review, we introduce the emerging roles of ncRNAs, including microRNAs (miRNAs), transfer-RNA-derived fragments (tRFs), long ncRNAs (lncRNAs), and circular RNAs (circRNAs), in the mitochondrial ETC and OXPHOS regulation.